Deciphering the impacts of modulating the Wnt-planar cell polarity (PCP) pathway on alveolar repair - Kim, Sally Yunsun; McTeague, David; Cheong, Sek-Shir; Hind, Matthew; Dean, Charlotte H. (Frontiers in Cell and Developmental Biology, 2024)
Many adult lung diseases involve dysregulated lung repair. Deciphering the molecular and cellular mechanisms that govern intrinsic lung repair is essential to develop new treatments to repair/regenerate the lungs. Aberrant Wnt signalling is associated with lung diseases including emphysema, idiopathic pulmonary fibrosis and pulmonary arterial hypertension but how Wnt signalling contributes to these diseases is still unclear. There are several alternative pathways that can be stimulated upon Wnt ligand binding, one of these is the Planar Cell Polarity (PCP) pathway which induces actin cytoskeleton remodelling. Wnt5a is known to stimulate the PCP pathway and this ligand is of particular interest in regenerative lung biology because of its association with lung diseases and its role in the alveolar stem cell niche. To decipher the cellular mechanisms through which Wnt5a and the PCP pathway affect alveolar repair we utilised a 3-D ex-vivo model of lung injury and repair, the AIR model. Our results show that Wnt5a specifically enhances the alveolar epithelial progenitor cell population following injury and surprisingly, this function is attenuated but not abolished in Looptail (Lp) mouse lungs in which the PCP pathway is dysfunctional. However, Lp tracheal epithelial cells show reduced stiffness and Lp alveolar epithelial cells are less migratory than wildtype (WT), indicating that Lp lung epithelial cells have a reduced capacity for repair. These findings provide important mechanistic insight into how Wnt5a and the PCP pathway contribute to lung repair and indicate that these components of Wnt signalling may be viable targets for the development of pro-repair treatments.